2009
DOI: 10.1007/s00041-009-9066-0
|View full text |Cite
|
Sign up to set email alerts
|

Pointwise Estimates for Laplace Equation. Applications to the Free Boundary of the Obstacle Problem with Dini Coefficients

Abstract: In this paper we are interested in pointwise regularity of solutions to elliptic equations. In a first result, we prove that if the modulus of mean oscillation of ∆u at the origin is Dini (in L p average), then the origin is somehow a Lebesgue point of continuity (still in L p average) for the second derivatives D 2 u. We extend this pointwise regularity result to the obtacle problem for the Laplace equation with Dini right hand side at the origin. Under these assumptions, we prove that the solution to the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Following the proof of Lemma 2.9 in [13], we consider a dyadic decomposition of the cylinder Q − ρ , and estimate the quantities in each sub-cylinder. More precisely, we get for 1 ≤ ρ = 2 k r with r ∈ [1/2, 1) that…”
Section: Some Routine Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the proof of Lemma 2.9 in [13], we consider a dyadic decomposition of the cylinder Q − ρ , and estimate the quantities in each sub-cylinder. More precisely, we get for 1 ≤ ρ = 2 k r with r ∈ [1/2, 1) that…”
Section: Some Routine Resultsmentioning
confidence: 99%
“…Given (u, f ) and λ ∈ (0, 1), let us introduce the notation Contrarily to what is done in [13], the functions N and ω are not necessarily monotone in r. Nevertheless, we have the following routine result (the analogue to Lemma 3.4 in [13]). for some constants C 0 > 0, λ, µ ∈ (0, 1) and assume that ω is Dini.…”
Section: Some Routine Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monneau, [Mon09], observed that if f is a harmonic function vanishing to first order at x 0 and p is a 1-homogenous polynomial then M x 0 is monotonically decreasing as r ↓ 0.…”
Section: Monneau Monotonicity and Non-degeneracymentioning
confidence: 99%
“…In the same paper (under the same hypotheses of coefficients) the three authors proved a generalization of the monotonicity formula introduced by Monneau [36] to analyze the behaviour near the singular points (see Definition 6.6). In [37] he improved his result; he showed that his monotonicity formula holds under the hypotheses that A ≡ I n and f with a Dini modulus of continuity in an L p sense. In [24] Garofalo and Petrosyan showed the formula of Monneau for the thin obstacle with a regular obstacle.…”
Section: Introductionmentioning
confidence: 97%